Identifikasi Molekuler Begomovirus Penyebab Penyakit Kuning Keriting pada Tanaman Cabai (Capsicum annum L.) di Sumatera Barat - Trisno, Jumsu; Hidayat, Sri Hendrastuti; Jamsari, Jamsari; Habazar, Trimuri; Manti, Ishak (Jurnal Natur Indonesia, 2010)
Pepper plants showing Begomovirus-like symtoms, consisting of yellowing, leaf curling, and distortion, werecollected from fields located in the Padang, West Sumatra. The aim of this research is to identification ofbegomovirus associated with yellow leaf curl diseases on pepper. Total DNA was extracted from infected leaftissue according to Doyle and Doyle (1999) with slight modification. Polymerase chain reaction (PCR) was used toamplify the coat protein region of the virus using universal degenerate primers pAV494 and pAC1048. The PCRamplified DNA product (approx. 560 bp) was sequenced. The nucleotide and amino acid sequences and BLASTsearch revealed highest homology with pepper yellow leaf curl Indonesia virus isolated pepper, tomato andAgeratum conyzoides from Java, but differences from those of tomato yellow leaf curl virus. The isolate was thententatively called pepper yellow leaf curl Indonesia virus-Padang (PYLCIV-Pdg).